Optimalisasi Potensi Ekonomi Lokal Berbasis Industri Halal Melalui Seminar Kewirausahaan Bagi Masyarakat Desa Kalimas Kabupaten Kubu Raya - Kalbarini, Rahmah Yulisa; Zulinda, Nia; Ariza, Anggatia; Nurjannah, Syamratun; Atikha, Suci; Bilhaq, M. Agus Muhtadi; Saragih, Eka Junila; Helvira, Reni; Elisa, Ema; Gunawan, M. Wawan; Ulum, Bahrul; Jayanti, Fitri; Khairunnisa, Dina; Novita (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Local economic potential must be explored and developed in order to improve the local economy. The involvement of various stakeholders is necessary to accelerate regional economic development. One of significant contribution by the FEBI IAIN Pontianak academician society is the community service activities that held in Kalimas Village. This community service consist of entrepreneurship seminary and FGD which aims to explore local potential based on the halal industry as well as assistance with Halal Products and Halal Product Certification. In this activity, information was obtained regarding potential in the tourism sector and processing of natural wealth. If this potential can be managed, it can support the export value of the halal industry, the potential for halal tourism, and strengthen the role of the sharia financial sector in achieving financial inclusion.